2023
DOI: 10.3390/ma16093525
|View full text |Cite
|
Sign up to set email alerts
|

Clean H2 Production by Lignin-Assisted Electrolysis in a Polymer Electrolyte Membrane Flow Reactor

Abstract: Biomass-derived products, such as lignin, are interesting resources for energetic purposes. Lignin is a natural polymer that, when added to the anode of an alkaline exchange membrane water electrolyser, enhances H2 production rates and efficiencies due to the substitution of the oxygen evolution reaction. Higher efficiencies are reported when different catalytic materials are employed for constructing the lignin anolyte, demonstrating that lower catalytic loadings for the anode improves the H2 production when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Recently, there has been a resurgence of interest in the production of green hydrogen using these reactors, with various mechanisms being explored. 6,7 Many authors have shown interest in exploring design aspects of these units. In Refs.…”
mentioning
confidence: 99%
“…Recently, there has been a resurgence of interest in the production of green hydrogen using these reactors, with various mechanisms being explored. 6,7 Many authors have shown interest in exploring design aspects of these units. In Refs.…”
mentioning
confidence: 99%